2014
DOI: 10.1093/mnras/stt2334
|View full text |Cite
|
Sign up to set email alerts
|

The distance to the young cluster NGC 7129 and its age

Abstract: The dust cloud TGU H645 P2 and embedded in it young open cluster NGC 7129 are investigated using the results of medium-band photometry of 159 stars in the Vilnius seven-colour system down to V = 18.8 mag. The photometric data were used to classify about 50 % of the measured stars in spectral and luminosity classes. The extinction A V vs. distance diagram for the 20 ′ × 20 ′ area is plotted for 155 stars with two-dimensional classification from the present and the previous catalogues. The extinction values foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Many of the pre-main sequence stars found in the Cepheus flare are part of this region (Kun et al 2008). NGC 7129, however, seems to be at a larger distance of 1 kpc (Racine 1968;Straižys et al 2014).…”
Section: Star-forming Regions In Gould Beltmentioning
confidence: 87%
“…Many of the pre-main sequence stars found in the Cepheus flare are part of this region (Kun et al 2008). NGC 7129, however, seems to be at a larger distance of 1 kpc (Racine 1968;Straižys et al 2014).…”
Section: Star-forming Regions In Gould Beltmentioning
confidence: 87%
“…the Hα emission and X-ray detected sources, are superposed in the figure. The zero age main sequence (ZAMS) of Siess et al (2000) is overplotted using the dwarf colors presented by Kenyon & Hartmann (1995) and assuming a distance of 1150 pc (Straižys et al 2014). The cluster sequence is welldefined by the activity-selected sample and lies at least two magnitudes above the ZAMS, even for the early-type members.…”
Section: The Color-magnitude Diagram Of the Cluster Populationmentioning
confidence: 99%
“…Magakian et al (2004) concluded that most of the detected Hα emission sources were T Tauri stars. Vilnius 7color photometry down to V =18.8 is provided by Straižys et al (2014) for 159 stars in the cluster region. The photometric data was used to classify about half of the detected sources, assigning spectral types, luminosity classes and deriving extinction estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five members fulfil both astrometric and photometric condition, they are stars No. 1 (UCAC4 781-037989 Straižys et al [11] find that the young age of the cluster makes that only six While comparing our results with these six cluster members, it can be seen that only star No. 105 (UCAC4 781-037982) does not fulfil the astrometric membership condition due to its proper motion.…”
Section: Open Cluster Vdb146mentioning
confidence: 53%